Prognosis and clinical issues of esophageal atresia in extremely low birth weight neonates: a case series - Masaki Horiike; Hitomi Mimura; Akiko Yokoi (BMC, 2023)
Abstract Background Esophageal atresia (EA) in extremely low birth weight (ELBW) neonates is rare. This report aims to clarify EA's clinical courses and prognosis in ELBW neonates and the clinical issues of long-term survival cases. Methods A retrospective analysis was conducted for 8 neonates diagnosed with esophageal atresia. Medical records of ELBW EA neonates treated at our institution were reviewed to assess patient demographics, clinical courses, and outcomes. Transferred patient data was obtained from their local physicians through questionnaires. Results EA in ELBW neonates were included in 8 of EA infants (7%). Fatal respiratory and cardiovascular complications of trisomy 18 and complications related to immaturity such as liver failure and pulmonary hypertension were associated with poor prognosis. During primary operations, gastrostomy and esophageal banding were performed together in 50% of the cases, while gastrostomy was performed alone in 25%. The esophageal anastomosis was not performed during any primary operation. All causes of death, except for 1 case, were due to non-surgical causes. A long-term survival case of 17 years postoperatively was included. Conclusion Although ELBW EA has a poor prognosis, long-term survival is possible in some cases, so aggressive therapeutic intervention is considered essential. It is important to share information about the prognosis with parents and multidisciplinary specialists and to select an appropriate treatment strategy for each case.